Rubus zielinskii (Rosaceae), a new species from Poland - Wolanin, Mateusz Marian; Wolanin, Magdalena Natalia; Musiał, Krystyna; Kania, Iwona; Oklejewicz, Krzysztof (Phytotaxa, 2016)
Rubus zielinskii M. M. Wolanin & M. N. Wolanin, a new species from south-east Poland is described and illustrated. Rubus zielinskii is a tetraploid (2n=28) belonging to the series Sprengeliani based on morphology. It is most similar to Rubus sprengelii from which it differs in the inflorescence, being leafy to the apex, the larger flowers, paler colour of the vegetative stem and straighter prickles. The species occurs mostly along forest roads, ditches and forest edges. A species conservation assessment for Rubus zielinskii determines its threat status to be Least Concern.